Molecular cloning of gene fragment encoding 4-coumarate: Coenzyme A ligase of Sengon (Paraserianthes falcataria) - Hartati, Sri N.; Sudarmonowati, Enny; S, Suharsono; Sofyan, Kurnia (Indonesian Journal of Biotechnology, 2010)
4-coumarate:Coenzyme A ligase (4CL) plays an important role in lignin biosynthetic pathway thatcatalyzed the activation of coumaric acid, caffeic acid or ferulic acid to be a syringil monomer. Ligninbiosynthesis control through 4CL down regulating would support lower lignin wood production. Theobjective of this study was to clone conserved region cDNA of gene encoding 4CL. Gene fragment isolation wasconducted by means of reverse transcriptase polymerase chain reaction (RT-PCR) using degenerateheterologous primer. The RT-PCR products were purified, sequenced and analyzed to select the highlyhomologous fragment to 4CL. BLASTanalysis result showed that deduction of amino acid sequences from oneof two RT-PCR product nucleotide was highly homologous with the 4CL conserved region from Rubbus ideaus,Oryza sativa, Populus tomentosa, Populus balsamifera, Betulla platyphilla, Nicotiana tabacum, and Arabidopsisthaliana with identity ranging from 78-90%.Key words: 4-coumarate: Coenzyme A ligase, lignin, sengon